An Analysis of Students’ Errors on the Use of Passive Voice in Writing Recount Text (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
Researchers often find that there are students' error' in using passive on writing texts. Applying proper grammar in writing recount text is usually a problem for students. The purpose of this study was to clasify the errors and the causes of English Literature students in using passive voice on their recount text writings at Pamulang University. Qualitative descriptive method was used to approach the data. The population in this study are about 200, third semester students of Unpam English Literature Department. Researchers take 20 students to represent the population sample with purposive sampling technique. The instrument is students’ recount texts. Researchers ask students to write down their unique experiences. Researchers collect data, identify data, classify passive voice errors and explain the causes of students’s errors in using passive voice on recount text. Students’ errors are classified into four categories based on the types of errors, they are omission errors, addition errors, misformation errors, and misordering errors. After finishing this research, researchers are expected to enrich lecturer and student knowledge and improve students' ability in useing passive sentences in writing recount text, and to find out the types and the causes of students' errors in using passive sentences in writing recount texts.